Faktor pengaruh kepuasan kerja terhadap kinerja para karyawan - Ramadan Pasaribu; Siti Nur Hasanah; Aprilia Kinanti; Wahyu Pinastia Ningrum; Reva Kirana Putri (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Job satisfaction has a significant impact on employee performance and work outcomes. The purpose of this study is to provide a literature review of the various factors that influence employee job satisfaction and to fill the gaps in the previous literature that are the gaps in this study. The approach used in this study is a systematic literature review. Data were obtained by conducting an internet search on employee job satisfaction using keywords such as job satisfaction, employee satisfaction, employee job satisfaction, and others. There were 15 journals analyzed in this study. Data analysis was conducted using a qualitative approach. The findings of this study indicate six factors that contribute to job satisfaction, namely job content (autonomy and role clarity), management (performance evaluation and support from management), work environment (physical conditions, relationships between superiors and subordinates, and relationships with fellow coworkers), compensation (rewards), job promotion (promotion system and employment aspects), and training (regular and effective training)